Equity and trusts - Clements, Richard (Oxford University Press, 2009)
Complete Equity and Trusts provides a blend of explanatory text, cases and materials making it ideal for students new to equity and trusts. In this student-centered and approachable text, complex topics are explained clearly and succinctly. Well-integrated extracts from essential case law illustrate the key legal principles and precedents, and demonstrate their significance. A range of learning features stimulate active engagement with the subject and support students' understanding of the law